2022
DOI: 10.1186/s12885-022-09289-7
|View full text |Cite|
|
Sign up to set email alerts
|

SNCA correlates with immune infiltration and serves as a prognostic biomarker in lung adenocarcinoma

Abstract: Background The SNCA gene is a critical gene in Parkinson’s disease (PD) pathology. Accumulating evidence indicates that SNCA is involved in tumorigenesis; however, the role of SNCA in lung adenocarcinoma (LUAD) remains unclear. This study aimed to explore the potential value of SNCA as a prognostic and diagnostic molecular marker in LUAD. Methods In this study, we explored the expression pattern, prognostic value, and promoter methylation status of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 74 publications
(27 reference statements)
0
13
0
Order By: Relevance
“…20 Moreover, exosome proteomics revealed distinct integrin expression patterns, in which the exosomal integrin αVβ5 was linked to liver metastasis, while exosomal integrins α6β4 and α6β1 were associated with lung metastasis. 30 Notably, α-syn was expressed in both the central nervous system 8 and various tumors, [11][12][13][14] and toxic phosphorylation of α-syn at S129 was also detected in melanoma cells and secreted vesicles. 15 Thus, the above results suggested a role of α-syn-containing exosomes in distance communication between PD and peripheral cancer, and it is reasonable to speculate that exosomes from PD patients might deliver α-syn in regulating liver cancer.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…20 Moreover, exosome proteomics revealed distinct integrin expression patterns, in which the exosomal integrin αVβ5 was linked to liver metastasis, while exosomal integrins α6β4 and α6β1 were associated with lung metastasis. 30 Notably, α-syn was expressed in both the central nervous system 8 and various tumors, [11][12][13][14] and toxic phosphorylation of α-syn at S129 was also detected in melanoma cells and secreted vesicles. 15 Thus, the above results suggested a role of α-syn-containing exosomes in distance communication between PD and peripheral cancer, and it is reasonable to speculate that exosomes from PD patients might deliver α-syn in regulating liver cancer.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that overexpression of α‐syn increased the vulnerability of neurons to dopamine‐induced cell death through excess intracellular reactive oxygen species generation in PD cellular model, 9 and phosphorylation at Ser129 was essential for α‐syn‐induced neurotoxicity in a drosophila model of PD 10 . Notably, α‐syn is widely distributed in peripheral tissue cells such as lung adenocarcinomas, pancreatic ductal adenocarcinomas, colorectal cancers, and bladder cancer 11–14 and toxic phosphorylation of α‐syn at Ser129 is also detected in secreted vesicles from melanoma cells 15 . It is also that α‐syn could inhibit the proliferation of lung adenocarcinoma cells via inhibiting PI3K/AKT/mTOR signaling pathway 11 and bladder cancer cell proliferation by arresting the cell cycle in the S phase via upregulation of p53 expression mediated by DNA damages 14 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Following publication of the original article [ 1 ], the authors identified an error in the order of the figures. The correct order is given below.…”
mentioning
confidence: 99%